Assessment of Economic Benefits Flowing from Collection of Non Wood Forest Products in South Dangs Forest Division, Gujarat, India - Yadav, Rajkumar S.; Rajpurohit, Sweta; Kamboj, Ravi Dutt; Pandya, Ishan (Indian Forester, 2019)
Non Wood Forest Products (NWFPs) are important goods that act as a source of subsistence of forest dwellers living in the vicinity or within forest areas. In the present study, an attempt has been made to quantify collection of different types of NWFPs and the associated economic benefits derived by the communities in South Dangs Forest Division (SDFD). The study was conducted through primary survey of forest dwellers in SDFD using structured questionnaire. From the study, 25 types of NWFPs which have been classified into 6 groups namely, leaves, flowers and seeds, culms and stems, fruits, gums and miscellaneous forms were found to be collected by local peoples. The study revealed estimated economic benefits of ₹124.41 lakhs/annum of which the economic benefits derived from collection of fruits was ₹34.3 lakhs/ annum, culm and stem was ₹31.59 lakhs/annum, flowers and seeds was ₹27.14 lakhs/annum, leaves was ₹19.76 lakhs/annum, miscellaneous forms was ₹7.41 lakhs/annum and gums was ₹4.21 lakhs/annum. The study also revealed that economic benefits of NWFPs collection to the local tribal people is available throughout the year and provide to be an important source of their livelihood.